POST-GLACIAL REBOUND AND PRESENT-DAY THREE-DIMENSIONAL DEFORMATIONS - Plag H.P.; Engen B.; Clark T.A.; Degnan J.J.; Richter B. (My University, 1998)
The WEGENER# activities related to the study of post-glacial rebound are presented together with a review of the present state-of-the-art in this study field. Post-glacial rebound research is an unique tool for studying the viscoelastic behaviour of the Earth's mantle on time scales of thousands of years. The viscosity structure of the Earth's mantle determined from an inversion of observations of glacially induced deformations is a basic requirement for modelling long-term phenomena such as the convection in the Earth's mantle, and for better understanding unsolved questions such as the nature of the mantle discontinuities or the vertical scale of convection.First, an introduction to the scientific background is given, and the three principal ingredients for post-glacial rebound studies, namely the ice model, the Earth model, and the observations are briefly considered. For the ice model, the uncertainties due to a trade-off between ice model and Earth rheology are outlined. The different approaches used to model the Earth and its deformations in post-glacial rebound studies are discussed emphasising the preliminary nature of the derived rheologies and depth dependencies. The observations, in particular the relative sea-level changes and three-dimensional surface deformations, are described with special emphasis on observational gaps. Based on the discussion of the ingredients, an outline of the future developments in post-glacial rebound research is attempted with particular emphasis on the Earth model and the theory of deformations.For several decades extreme efforts have been made to precisely monitor the land uplift in Scandinavia. However, for the height component the existing data still are associated with large uncertainties while reliable data on the horizontal component are practically nil. The ongoing long-term (longer than ten years) spacegeodetic measurements are likely to provide the three-dimensional deformations with the spatial resolution and accuracy required in order to substantially contribute to post-glacial rebound studies. Thus, present-day three-dimensional deformations of the Earth's surface beneath and around the former ice sheets as a constraint for the mantle rheology and viscosity structure will increasingly become important as they become known from space-geodetic measurements with high spatial resolution and an accuracy approaching the mm/a-level.